2015
DOI: 10.1080/02755947.2015.1035467
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Ability of Tiger Muskellunge to Eradicate Brook Trout in Idaho Alpine Lakes

Abstract: In western North America, nonnative Brook Trout Salvelinus fontinalis in alpine lakes threaten the persistence of native trout and often offer limited sport fishing opportunity as they are prone to stunting. Stocking tiger muskellunge (Northern Pike Esox lucius × Muskellunge E. masquinongy), which are reproductively sterile, may be an option to eradicate Brook Trout in some alpine lakes. We used floating gill nets to survey 17 alpine lake Brook Trout populations, then stocked 13 lakes with tiger muskellunge, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 45 publications
0
22
0
Order By: Relevance
“…Results from this experiment indicate that turbidity could negatively impact the foraging success of and reduce selectivity by tiger muskellunge in turbid systems. Due to 490 their highly piscivorous nature and ability to control populations of undesirable fish species (e.g., White Sucker Catostomus commersonii and Black Crappie Pomoxis nigromaculatus: Siler and Beyerle 1986; Brook Trout Salvelinus fontinalis: Koenig et al 2015), tiger muskellunge are used as a biological control agent, but based on our results, this strategy may be ineffective in lakes where Secchi depths average 26 cm or less. Furthermore, survival and recruitment of stocked tiger muskellunge may be affected, in part, by low food consumption when Secchi depths are 26 cm or less.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Results from this experiment indicate that turbidity could negatively impact the foraging success of and reduce selectivity by tiger muskellunge in turbid systems. Due to 490 their highly piscivorous nature and ability to control populations of undesirable fish species (e.g., White Sucker Catostomus commersonii and Black Crappie Pomoxis nigromaculatus: Siler and Beyerle 1986; Brook Trout Salvelinus fontinalis: Koenig et al 2015), tiger muskellunge are used as a biological control agent, but based on our results, this strategy may be ineffective in lakes where Secchi depths average 26 cm or less. Furthermore, survival and recruitment of stocked tiger muskellunge may be affected, in part, by low food consumption when Secchi depths are 26 cm or less.…”
Section: Discussionmentioning
confidence: 95%
“…Tiger muskellunge (Northern Pike × Muskellunge) are stocked into aquatic systems throughout North America (Crossman 1986;Wahl et al 2012) to control overabundant or undesirable fish species (Lepak et al 2014;Koenig et al 2015;Sorel et al 2016) or to create sport fisheries (Wahl et al 2012;Sorel et al 2016). Numerous studies have evaluated variables that may affect the survival of tiger muskellunge, including the use of artificial (pellet) versus natural (fish) diets administered prior to stocking (Gillen et al 1981); predation Wahl and Stein 1989); and predator acclimation (Wahl et al 2012).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Most recently, tiger muskellunge (Northern Pike Esox lucius × Muskellunge E. masquinongy ) have been introduced into alpine lakes and have successfully eradicated Brook Trout in some (but not most) of them (Koenig et al. ). The mixed success of these methods identifies the need for additional methods for nonnative fish eradication.…”
mentioning
confidence: 99%
“…Intensive gillnetting has eradicated Brook Trout populations in a few alpine lakes (e.g., Knapp and Matthews 1998;Parker et al 2001), although this technique may be effective only in lakes smaller than 3 ha in size (Knapp and Matthews 1998). More recently, tiger muskellunge (Northern Pike Esox lucius × Muskellunge E. masquinongy) have been used to eradicate Brook Trout in some alpine lakes, but the technique appears to be ineffective in lakes with inlets or outlets because Brook Trout continue to reside in flowing-water areas not inhabited by tiger muskellunge (Koenig et al 2015). In the most comprehensive study to date on population effects of Brook Trout removal in alpine lakes, Hall (1991) concluded that methods designed to reduce recruitment should be evaluated because massive density reductions alone were not effective in suppressing larger populations.…”
mentioning
confidence: 99%